Management of Skull Fractures and Calvarial Defects - Vincent, Aurora; Sokoya, Mofiyinfolu; Shokri, Tom; Gordin, Eli; Inman, Jared C.; Manolidis, Spiros; Ducic, Yadranko (Facial Plastic Surgery, 2019)
Scalp and calvarial defects can result from a myriad of causes including but not limited to trauma, infection, congenital malformations, neoplasm, and surgical management of tumors or other pathologies. While some small, nondisplaced fractures with minimal overlying skin injury can be managed conservatively, more extensive wounds will need surgical repair and closure. There are many autologous and alloplastic materials to aid in dural and calvarial reconstruction, but no ideal reconstructive method has yet emerged. Different reconstructive materials and methods are associated with different advantages, disadvantages, and complications that reconstructive surgeons should be aware of. Herein, we discuss different methods and materials for the surgical reconstruction of calvarial defects.
Keywords: scalp soft tissue repair; dural repair; skull fractures; calvarial reconstruction